Urokinase Excretion in Man: A Method of Determination and Consideration of its Significance - von Kaulla, Kurt N.; Riggenbach, Neil (Thrombosis and Haemostasis, 1961)
A simple method is described for the quantitative determination of urokinase, a plasminogen activator, in human urine. Plasminogen activation by urokinase and the measurement of the proteolytic activity of the formed plasmin are separated in two individual steps. The normal urokinase excretion values for males and females in various conditions are discussed. Examples of pathological excretion patterns are also given.